My teacher said this is incorrect because I should be taking the natural log of both sides of the equation. How would I do that?
y = e^3
y = e^3
e = 3SQRT(y)
e = y^1/3
e^2 = y^2/3
Thanks
remember that when you have y = b ^ x, this can be written as log_b y = x.
In this case, b = e, so log_e (y) = 3. Log to base e is written ln, so this becomes ln (y) = 3.
But, it's not clear to me what problem you are really trying to solve. Are you trying to solve for y? If so, just compute e^3 on your calculator, and that's the answer.
Posted and discussed here: http://www.mathhelpforum.com/math-he...n-correct.html
Thread closed.